Crohn's disease - genetic factors and progress of the disease - Kupka, Tomas; Simova, Jarmila; Dvorackova, Jana; Martinek, Lubomir; Motyka, Oldrich; Uvirova, Magdalena; Dite, Petr (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
BACKGROUND AND OBJECTIVES: Crohn's disease is a multifactorial inflammatory disease affecting mainly the gastrointestinal tract. The genetic factors that are involved in the disease include mainly three mutations of the gene NOD2/CARD15 (R702W, G908R, 3020insC). The aim of this study was to determine the relationship between the presence of these variants and disease phenotype. MATERIAL AND METHODS: 70 patients with Crohn's disease were examined for the presence of the above-mentioned mutations. The researchers used the medical records to retrospectively obtain clinical data and together with the information obtained prospectively according to the protocol they analysed the connection between gene mutations and disease phenotype. RESULTS: At least one mutation was found in 22 patients with Crohn's disease (32%), four patients were found to have two different mutations (composed heterozygotes - 6%) and six patients (9%) were homozygotes for the 3020insC gene. No significant differences were found between the groups with wild-type form and the mutated form of the NOD2 / CARD15 gene with respect to age at the time of diagnosis, form of the disease or localization according to the Montreal classification. CONCLUSION: Mutations of the NOD2 / CARD15 gene did not significantly affect the frequency of reoperations, homozygotes with 3020insC gene mutations, however, represented a high risk group. The phenotype was not related significantly to the presence of the examined mutations.
Keywords: senioři; Genetic Predisposition to Disease; NOD/CARD15; Homozygote; reoperace; Montreal classification; Heterozygote; Nod2 Signaling Adaptor Protein; Crohn's disease; Middle Aged; mužské pohlaví; mutace; Crohnova nemoc; Prospective Studies; Adult; mladý dospělý; fenotyp; Reoperation; Phenotype; Young Adult; ženské pohlaví; Mutation; Humans; prospektivní studie; signální adaptorový protein Nod2; lidé středního věku; homozygot; Crohn Disease; dospělí; genetická predispozice k nemoci; Female; Aged; lidé; Male; heterozygot